2019
DOI: 10.1016/j.ejso.2019.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Autologous fat transfer after breast cancer surgery: An exact-matching study on the long-term oncological safety

Abstract: Introduction: Autologous fat transfer (AFT) is widely adopted for breast reconstruction, but its longterm oncologic safety is still not clearly established. The aim of the present study was to compare the 10-year loco-regional recurrence (LRR)-free and distant metastases (DM)-free survival probabilities in AFT vs. control patients, also evaluating the impact of AFT in different intrinsic molecular subtypes of breast cancer. Materials and Methods: 464 AFT patients were exactly matched with a cohort of 3,100 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 32 publications
0
25
0
1
Order By: Relevance
“…Petit et al (29) and presented 2 studies showing an increase of LRR when the lipofilling is performed within the first 3 years after the oncologic surgery. However, Sorrentino et al (30) divides the interval in the first year after the oncologic surgery and within the second and third years after the oncologic surgery, with no statistically significant differences found in the total of LRR. Our study does not show statistically significant differences in the rate of LRR in the patients receiving the lipofilling within the first 3 years after the oncologic surgery and the ones after that (log-rank P value =0.317).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Petit et al (29) and presented 2 studies showing an increase of LRR when the lipofilling is performed within the first 3 years after the oncologic surgery. However, Sorrentino et al (30) divides the interval in the first year after the oncologic surgery and within the second and third years after the oncologic surgery, with no statistically significant differences found in the total of LRR. Our study does not show statistically significant differences in the rate of LRR in the patients receiving the lipofilling within the first 3 years after the oncologic surgery and the ones after that (log-rank P value =0.317).…”
Section: Discussionmentioning
confidence: 99%
“…Table 5 shows the incidence of LRR (%LRR), incidencedensity rates (LRR/year), follow-up time and number of patients included in our study sample compared to other published studies with similar characteristics (14,16,17,30,32). Our study shows a LRR rate of 2.4% and an incidence-density rate of 0.61%/year.…”
Section: Discussionmentioning
confidence: 99%
“…However, no clinical study has significantly demonstrated the impact of AFT on locoregional recurrence or distant metastasis in relation to BC molecular subtypes probably because of unbalanced stratifications in different subtypes or no sufficiently long follow-up times. In 2019, Sorrentino et al reported a possible increase in late locoregional recurrence for Luminal A patients treated by AFT [155]. Despite this intriguing finding, it should be noted that only less than one-third of the initial Luminal A population was still on follow-up after 80 months, being aware of the correlation of Luminal cancers to late recurrences.…”
Section: Open Questionsmentioning
confidence: 99%
“…Sorrentino et al performed a sub-analysis examining fat grafting and locoregional recurrence and distant metastases showed no increase in rate of recurrence during follow-up. However, their predictive model demonstrates that after 80 months, there would be a statistically significant greater recurrence rate in patients with Luminal A cancers that underwent lipofilling compared to the matched control Luminal A cancers that did not undergo lipofilling (23). There was a statistically significant difference in Her-2 expression between study arms in two studies: Silva et al 2017 included 19.5% Her-2 positive in the lipofilling group vs. 28% in the control group (P=0.022) (20); Gale et al included 15% Her-2 positive in the lipofilling group vs. 7.3% in the control group (P=0.013), but 37% of patients in the lipofilling group and 52.4% of patients in the control group had an unknown Her-2 status (11).…”
Section: Comparison Groupmentioning
confidence: 99%